In the Shadow of Boone and Crockett : Race, Culture, and the Politics of Representation in the Upland South - Hartman, Ian C. (Book collections on Project MUSE., 2015)
"As Theodore Roosevelt's lofty image of frontier whites in the mold of Daniel Boone and Davy Crockett lost its luster, a realistic image of poor, isolated Appalachians rose to the forefront of America's cultural mindset. Hartman traces the disparaging lengths that state governments and various other organizations went to in order to shun the image of poor, racially inferior Appalachia and present (and preserve) a more unified, white Appalachia. Hartman discusses the ideals of masculinity in the age of U.S. imperialism, the career of Oscar McCulloch and the Indiana Solution, sterilization laws in Virginia, and the war on poverty in the mid-twentieth century. Hartman argues that these were all attempts to preserve the racial purity of Appalachian and even Southern white populations and to raise poor whites to a position of power over other races"--